komposisi jenis dan struktur hutan hujan tropika dataran rendah di taman nasional danau sentarum, kalimantan barat - Cecep Kusmana; Bambang Hero Saharjo; Basuki Sumawinata; . Onrizal; Tsuyoshi Kato (Institut Pertanian Bogor, 2009)
The objective of this research was to obtain information on species composition and structure of lowland tropical rain forest in Sentarum lake National Park, West Kalimantan. The research was carried out from 26 to 31 December 2003 and from 20 January to 5 February 2004 on the foot slope of Semujan Hill in Sentarum lake National Park. To carry out the research, 10 sample units SU'S) with size of 10 m x 10 m each, were placed, based on systematic sampling with random start scheme, with distance of 10 m between each SU. On each SU, trees with diameter 2 em were identified and diameter DBH) and height were recorded. Eighty four 84) tree species were found in a 0.1 ha SU, consisting of 32 families, dominated by 16 species of Dipterocarpaceae, followed by 9 species of Guttiferae and 5 species of Melastomataceae. Tree density decreased exponentially with increasing the diameter of trees.",